2015
DOI: 10.1097/qad.0000000000000679
|View full text |Cite
|
Sign up to set email alerts
|

Inferring HIV incidence from case surveillance with CD4+ cell counts

Abstract: This methodology provides a novel way of estimating population incidence by combining diagnosis dates and CD4 cell counts at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
1
10
1
Order By: Relevance
“…Our estimate of HIV prevalence falls between the self-reported 5% found in national household samples [ 2 , 3 ] and the 10% reported by GBM in larger cities [ 4 , 5 ]. Our estimate of undiagnosed HIV is considerably lower than that found in previous studies conducted at gay venues in Melbourne and Queensland [ 6 , 7 ] and slightly lower than that used in recent modelling of the Australian epidemic [ 8 , 9 ]. Internationally, our results indicate that undiagnosed HIV among Australian GBM is among the lowest seen in high-income countries with concentrated epidemics among GBM [ 11 15 ].…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Our estimate of HIV prevalence falls between the self-reported 5% found in national household samples [ 2 , 3 ] and the 10% reported by GBM in larger cities [ 4 , 5 ]. Our estimate of undiagnosed HIV is considerably lower than that found in previous studies conducted at gay venues in Melbourne and Queensland [ 6 , 7 ] and slightly lower than that used in recent modelling of the Australian epidemic [ 8 , 9 ]. Internationally, our results indicate that undiagnosed HIV among Australian GBM is among the lowest seen in high-income countries with concentrated epidemics among GBM [ 11 15 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Our study found a relatively low level of undiagnosed HIV among GBM in six Australian cities. The results suggest that recent modelling of the Australian epidemic may have slightly overestimated the burden of undiagnosed infection among GBM in metropolitan areas [ 8 , 9 ]. The profile of men with undiagnosed infection in our study highlights the ongoing need for HIV prevention and harm reduction programmes for GBM who have drug-based sex and condomless sex with casual partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… * For example Jansson et al . [ 39 ] proposed back-calculation based on complete data set of CD4 count. …”
Section: Discussionmentioning
confidence: 99%
“…For example, a novel method developed by Jansson et al . [ 39 ] estimates incidence and prevalence, making use of the date and value of first-recorded CD4 count.…”
Section: Living With Hivmentioning
confidence: 99%